Electrical and thermal performance assessment of photovoltaic thermal system integrated with organic phase change material - Ali Bhutto, Yasir; Pandey, Adarsh Kumar; Saidur, Rahman Md; Laghari, Imtiaz Ali; Khir, Hazim; Islam, Anas; Abu Zaed, Md (EDP Sciences, 2024)
The integration of photovoltaic (PV) system in power system proved to be potential technology in terms of renewable energy sources. However, photovoltaic system has major drawback of rise in cell temperature, which results in low power production and reduced service life. To overcome the temperature rise in photovoltaic system, the addition of water cooling and phase change materials installed at rear side PV system termed as photovoltaic thermal (PVT) system has been adopted in this study. The organic phase change material (RT-42) having melting temperature of 42 °C and water cooling running at 0.45 litre per minute (LPM) under 440 W/m2 irradiation has been taken as input parameters. The photovoltaic system and water cooled photovoltaic system performance has been analysed by using real time solar simulator. Additionally, the PVT-PCM system is assessed by use of TRNSYS simulation. Finally, this study compares the thermal and electrical efficiency of PV, PVT, and PVT-PCM systems. The findings indicated that maximum temperature for PV cells in a PV system was 59 °C. Water cooling alone reduces the temperature down to 49 °C, whereas water cooling combined with phase change material (PVT-PCM) lowers it down to 36°C. Further, the heat gain of 189 watt and 191 watt was achieved for PVT and PVT-PCM system. Additionally, the PV, PVT, and PVT-PCM systems achieved electrical efficiencies of 6.1%, 7%, and 9.5%, correspondingly.